Do Armário para a Cidadania: Políticas Públicas e Qualidade de Vida na População LGBTQIA+ - Tanizaka, Hugo (2020)
Increasingly in the fields of humanities and health, gender issues have played a prominent role in intellectual-scientific production, with this, more and more studies have been required to enable qualified understandings, aimed at the healthy development of the LGBTQIA + population. This dissertation aims to present data of relevance to the scientific community, since it presents a relevant panorama on health, gender violence and access to health services. The research used a mixed approach, that is, revealing quantitative and qualitative data, using the WHOQOL-BREF questionnaire, a socio-educational questionnaire and one created by the author about experiences in health services, and interviews with 3 participants screened by the results obtained in the WHOQOL-BREF. The data analyzes had phenomenological perspectives that allowed to understand the population's health issues from the participants themselves. The results achieved showed that of the 202 people who identified themselves as part of the LGBTQIA+ community, of these 34.7% said they had been discriminated against in public health services, 27.4% reported having suffered violence during health care, 33.6% declared they were not understood by professionals on specific issues about their gender and or sexuality. It was also possible to raise that 58.4% of the people who participated in the survey considered health services to be difficult to access and 65.8% stated that they had specific doubts about the health of the LGBTQIA + population. Through qualitative analyzes, notes emerged that showed the precariousness of information that health services have about the researched population, consequently occurring difficulties in the identification of situations of violence by the research participants; unsatisfactory understanding of what gender discrimination and violence really is; and ineffective distribution of systematized information that impairs access to health services. The survey also revealed that gender expressions by the health service follow a heteronormative norm, which affects damage to the healthy development of people who fall outside the standardized norm of gender and sexuality. Therefore, in the search for health and quality of life, the LGBTQIA+ population has restrictive access to rights, since the services do not provide integrality, universality and equity.